Neuropsychological functioning in children with and without specific learning disorder - Sarah Mufti; Misbah Arshad; Bushra Bibi (Journal of the Pakistan Medical Association, 2020)
Objective: To investigate neuropsychological functioning in children with and without Specific Learning Disorder. Methods: The comparative cross-sectional study was conducted in schools affiliated with Punjab Education Foundation, Gujrat, Pakistan, from January –to June 2019, and comprised children diagnosed with Specific Learning Disorder and age-matched and class matched high achievers as controls. Bender Gestalt Test II with copy test, recall test, perceptual test and motor test subscales was administered on both the groups for the assessment of neuropsychological functioning. Data was analysed using SPSS 21. Results: Of 116 subjects, 64(55.2%) were cases and 52(44.8%) controls. Overall, there were 64(55.2%) girls and 52(44.8%) boys with a mean age of 10.41(SD=1.14). There was significant difference on recall test (p<0.01) between the groups which had 100% predictive power. Conclusion: Memory function was significantly impaired in children with Specific Learning Disorder. Key Words: Specific learning disorder, Memory processing, Visuo-motor skills, Cognitive functioning.